Impact of fouling, cleaning and faecal contamination on the separation of water from urine using thermally driven membrane separation. Issue 9 (13th June 2018) - Kamranvand, F.; Davey, C.J.; Sakar, H.; Autin, O.; Mercer, E.; Collins, M.; Williams, L.; Kolios, A.; Parker, A.; Tyrrel, S.; Cartmell, E.; McAdam, E.J.
ABSTRACT: In this study, membrane distillation is evaluated as a technology for non-sewered sanitation, using waste heat to enable separation of clean water from urine. Whilst membrane fouling was observed for urine, wetting was not evident and product water quality met the proposed discharge standard, despite concentration of the feed. Fouling was reversible using physical cleaning, which is similar to previous membrane studies operating without pressure as the driving force. High chemical oxygen demand reduction was achieved following faecal contamination, but mass transfer was impeded and wetting occurred which compromised permeate quality, suggesting upstream intervention is demanded to limit the extent of faecal contamination.